Monstera limitaris (Araceae), a new species from the border between Costa Rica and Panama - Cedeño Fonseca, Marco Vinicio (2018)
Species of genus Monstera are among the most representative hemi-epiphytic Araceae in the Neotropics. They are widely distributed and abundant in the tropical forests of Costa Rica and Panama. During recent exploration in the border region between the two countries, an undescribed species belonging to the genus has been identified. The new species, Mostera limitaris, is described and illustrated here, using a color plate based on photographs of the vegetative and reproductive struc- tures of live material.